2016
DOI: 10.17533/udea.rfo.v28n1a12
|View full text |Cite
|
Sign up to set email alerts
|

Mesiodens. Reporte de caso.

Abstract: ABSTRACT. Mesiodens are supernumerary teeth, commonly seen in the maxillary midline. Given their high frequency, dentist should be aware of the signs and symptoms of mesiodens and their appropriate treatment. This case report describes an 8-year-old girl with a radiographic image suggesting two unerupted mesiodens between the central incisors on the palate. The intraoral examination showed swelling in the anterior INTRODUCCIÓNLos dientes supernumerarios tienen una prevalencia que oscila entre el 0,3 y el 3,8%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
1
0
4
Order By: Relevance
“…7 Quando localizado na linha média do palato entre os dois incisivos centrais superiores é denominado mesiodens. 3 Segundo Farias et al, 4 os mesiodens estão localizados na linha média da pré-maxila em 37% dos casos e na área dos incisivos centrais em 59%, já na região dos incisivos laterais atingem apenas 3%. Estes ainda afetam mais homens do que mulheres (2:1) 4 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…7 Quando localizado na linha média do palato entre os dois incisivos centrais superiores é denominado mesiodens. 3 Segundo Farias et al, 4 os mesiodens estão localizados na linha média da pré-maxila em 37% dos casos e na área dos incisivos centrais em 59%, já na região dos incisivos laterais atingem apenas 3%. Estes ainda afetam mais homens do que mulheres (2:1) 4 .…”
Section: Discussionunclassified
“…Os supranumerarios podem não entrar em erupção e afetar os incisivos superiores, causando reabsorção radicular, rotação axial, apinhamento, diastema e cistos dentígeros. 3 Sendo assim, em ambos os gêmeos optou-se pela extração dos supranumerários após o diagnóstico por tomografia computadorizada.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[5][6][7] La prevalencia general de los mesiodens es entre un 0.15 y 1.9%, donde la edad habitual de presentación clínica del quiste dentígero debido a un diente supernumerario es en las primeras cuatro décadas de la vida. 8 Los dientes supernumerarios pueden aparecer solos o múltiples, unilaterales o bilaterales, erupcionados o impactados, y aparecer tanto en el maxilar como la mandíbula. Se ha reportado que la dirección de erupción de mesiodens se puede dividir en tres formas: normal, horizontal o inversa, siendo la mayoría de los casos documentados de forma inversa 9,10 y cuya presencia puede generar complicaciones tales como impactación dentaria, apiñamiento, formación de diastemas, desplazamiento de dientes, interferencias oclusales, caries, problemas periodontales y formación de quistes dentígeros 11 como es el caso que se reporta.…”
Section: Introductionunclassified
“…[5][6][7] The prevalence in mesiodens is 0.15 to 1.9%; clinically, the dentigerous cyst due to a supernumerary tooth occurs in the first four decades of life. 8 In addition, supernumerary teeth may appear alone or multiple, unilateral or bilateral, erupted or impacted, and occur in the maxilla or mandible. It has been reported that the direction of mesiodens eruption may be regular, horizontal, or, the most frequent, inverse 9,10 and whose presence may generate complications such as dental impaction, crowding, diastema formation, tooth mobility, occlusal interference, caries, periodontal problems, and appearance of dentigerous cysts 11 as is the case that is reported.…”
Section: Introductionmentioning
confidence: 99%